Influence of key performance index toward job satisfaction, job stress and job turnover: A case of academic staff at Universiti Tunku Abdul Rahman, Perak, Malaysia - Kong, Chan Leong (2013)
The purpose of this study is to identify the influence of key performance index toward job satisfaction, job stress and job turnover. Nowadays, Malaysian academic policy is emphasizing the performance achievement of staff to enhance the quality of education. Thus this study was conducted to measure the academic staff regarding their response toward key performance index. Meanwhile, the academic staff of Universiti Tunku Abdul Rahman, Perak campus were selected for this study because it is merely new founded Malaysian University since year 2001, and this fledge environment assure that staff’s response is primitive. The questionnaire that used for this study consists of 4 main parts which were demographic survey, and total 41 survey items for variables of key performance index, job satisfaction, job stress and intention to leave (job turnover). Moreover, the distribution of questionnaire was conducted through sending email and hardcopy paper to respondent. The data were analyzed by the “Statistical Package for Social Science” (SPSS Window) Version 19.0. Correlation and multiple regression analysis were used to analyze the data. The findings showed that there is significant relationship between the independent variables (key performance index) and the dependent variable (job satisfaction and job stress). However, key performance index was found has no influence on job turnover for the staff in UTAR. Meanwhile, the multiple regression between dependent variables showed that the job stress and job satisfaction has significant relationship. The findings for this study will help the UTAR management to look further improvement and consideration of their performance evaluation system. Indeed, the findings from this study also can be the reference source for other academic institution especially to enhance its human resource practice